Acid-resistant solid catalyst for polyol oxidation reaction in water phase as well as synthesis method and application of acid-resistant solid catalyst
By modifying activated carbon with acid solution and loading Pt metal, the acid-resistant solid catalyst is synthesized, and the problem of unstable existing catalysts at high temperatures of aqueous oxidation is solved, the catalytic activity and acid resistance are improved, and the process efficiency is improved and economical.
Patent Information
- Application Number
- CN202411609072.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing activated carbon catalysts are unstable under the high-temperature catalytic system of aqueous oxidation, and have poor acid resistance, resulting in inactivation of active metals and unable to effectively catalyze the oxidation reaction of polyols.
By modifying the activated carbon with acid solution and loading the Pt metal by impregnation method, acid-resistant solid catalysts are synthesized, including steps such as activated carbon pretreatment, precious metal impregnation, calcination and high-temperature reduction.
It significantly enhances the catalytic activity and stability of the catalyst under complex aqueous phase systems, maintains good catalytic activity and acid resistance stability, improves the process, and reduces production energy consumption and investment.
Smart Images

Figure CN119455934A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to an acid-resistant solid catalyst for polyol oxidation reaction in water phase, a synthesis method and application thereof. Background Art
[0002] Activated carbon is a microcrystalline carbon material prepared by a series of processes such as carbonization and activation of carbon-containing raw materials such as wood and coal. It has a powdery, granular or pill-like appearance and is black in color. It has different pore structures inside and a large specific surface area (500-1700m 2 / g) and rich in surface chemical groups. This determines that activated carbon has good adsorption properties and has a good removal effect on organic pollutants in water such as benzene compounds, phenolic compounds, petroleum, methylene blue surfactants, herbicides, pesticides, synthetic dyes and many artificially synthesized organic compounds.
[0003] Activated carbon has a high surface area and developed porosity, relatively stable chemical properties, and easy recovery of the precious metals it carries, so it is often used as a catalyst carrier. The catalyst can be loaded on its surface by soaking the activated carbon in an aqueous solution of metal salts. In order to make it evenly dispersed, the activated carbon with oxidized surface must be used. Its performance as a carrier is determined by the pore structure and surface chemical structure. The chemical functional groups, surface heteroatoms and oxides on the surface determine the chemical properties of activated carbon. Catalysts that load platinum metals on activated carbon have excellent catalytic properties for the oxidation reaction of polyols such as glycerol and ethylene glycol. However, unmodified activated carbon is unstable in the catalytic system of high temperature of aqueous phase oxidation, and its acid resistance deteriorates, which will lead to problems such as deactivation of active metals. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide a method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in an aqueous phase, synthesizing a supported catalyst by an impregnation method, and modifying the surface properties of the activated carbon carrier to significantly enhance the catalytic activity and stability of the Pt / AC catalyst in a complex aqueous phase system.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] A method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in an aqueous phase comprises the following steps:
[0007] (1) Activated carbon pretreatment: adding activated carbon to an acidic solution, heating under reflux under stirring conditions, then cooling to room temperature, washing with deionized water until neutral, and drying to obtain pretreated activated carbon; the ratio of activated carbon to acidic solution is 1 g: 20-40 mL;
[0008] (2) Synthesis of acid-resistant solid catalyst: The pretreated activated carbon is added to the precious metal impregnation solution and mixed evenly, then aged at room temperature for 10 to 20 hours, taken out and crushed, calcined at elevated temperature, cooled, and reduced at high temperature to obtain the acid-resistant solid catalyst.
[0009] Preferably, the activated carbon in step (1) is wood activated carbon; the activated carbon has an active specific surface area of 1200 to 1600 m 2 / g, pore volume is 0.4~0.8cm 3 / g, and the average pore size is 2 to 2.5 nm.
[0010] Preferably, the heating reflux temperature in step (1) is 70-80° C., and the reflux time is 0.5-2 h.
[0011] Preferably, the acidic solution in step (1) is at least one of a nitric acid solution, a sulfuric acid solution and a hydrochloric acid solution; and the mass concentration of the acid in the acidic solution is 2-5%.
[0012] Preferably, the precious metal impregnation solution in step (2) is an aqueous solution of a platinum salt; the platinum salt is at least one of potassium chloroplatinate, tetraammine platinum nitrate, platinum nitrate, potassium chloroplatinite, ammonium chloroplatinite, chloroplatinic acid, and platinum acetylacetonate; the mass concentration of platinum in the precious metal impregnation solution is 1 to 10%; the amount of the precious metal impregnation solution is added according to the mass percentage of the precious metal element in the catalyst of 0.2 to 20wt%.
[0013] Preferably, the heating rate of the calcination in step (2) is 1.0-3.0°C / min, the temperature is 200-500°C, and the calcination time is 4-10h.
[0014] Preferably, the high temperature reduction in step (2) is carried out under H 2 / N 2 , H 2 / He、H 2 The mixture is carried out in at least one mixed atmosphere of H / Ar, wherein the mixed atmosphere contains H 2 The volume fraction of the mixed atmosphere is 10 to 30%, and the flow rate of the mixed atmosphere is 20 to 50 mL / min.
[0015] Preferably, the heating rate of the high temperature reduction in step (2) is 1.0 to 5.0° C. / min, the temperature is 200 to 500° C., and the reduction time is 4 to 10 h.
[0016] Another object of the present invention is to provide an acid-resistant solid catalyst for polyol oxidation reaction in water phase prepared by the above method, wherein the mass percentage of the noble metal element in the catalyst is 0.2-20wt%, wherein the mass of the active metal element is based on the mass of the metal element itself, and the mass of the catalyst is based on the mass of the catalyst itself.
[0017] The third object of the present invention is to provide a use of the above-mentioned catalyst, wherein the catalyst is used for the oxidation reaction of a polyol in an aqueous phase, and the polyol is at least one of glycerol, ethylene glycol, propylene glycol, butanediol, pentanediol, hexanediol, glucose, mannose, and xylose.
[0018] Preferably, the temperature of the oxidation reaction is 50-120° C., the reaction time is 0.5-48 h, and the oxygen pressure is 0.1-2.0 MPa.
[0019] Compared with the prior art, the present invention has the following beneficial effects: the present invention provides an acid-resistant solid catalyst for polyol oxidation reaction in water phase, a synthesis method and application thereof. The present invention modifies activated carbon by an acidic solution, loads a Pt metal synthetic catalyst by an impregnation method, and then dries, roasts, and reduces at high temperature, making full use of the excellent adsorption performance of activated carbon. The synthesized catalyst not only has uniformly dispersed active sites and maintains good catalytic activity in the polyol oxidation reaction, but also has good acid resistance and stability, which is conducive to improving the process and thus reducing production energy consumption and investment. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is the TEM image of the Pt / AC1 catalyst obtained in Example 1 at 20 nm. DETAILED DESCRIPTION
[0021] The present invention will be further described below in conjunction with the embodiments.
[0022] Example 1
[0023] A method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in an aqueous phase, comprising the following steps:
[0024] (1) Weigh 1 g of coconut shell activated carbon (specific surface area 1300 m 2 / g, pore volume is 0.5cm 3 / g, average pore size 2nm) was added to 20mL 3wt% HNO 3 The modified activated carbon was refluxed at 70°C for 1 h under electromagnetic stirring, and after cooling to room temperature, it was washed with deionized water until neutral, and dried to obtain the pre-treated activated carbon.
[0025] (2) Weigh 1 g of tetraammine platinum nitrate and dissolve it in 50 mL of deionized water to obtain a precious metal impregnation solution;
[0026] (3) 2 mL of the noble metal impregnation solution was mixed with 1 g of pre-treated activated carbon, and the mixture was aged at room temperature for 12 h in a cool and dry place. The mixture was then crushed and placed in a muffle furnace. The temperature was raised to 400 °C at a rate of 2 °C / min and then air-baked for 5 h. After cooling to room temperature, H was introduced. 2 The volume content of H is 20%. 2 / N 2 The mixed atmosphere (the flow rate of the mixed atmosphere is 30 mL / min.), the temperature is raised to 300° C. at a heating rate of 2° C. / min, and the catalyst Pt / AC1 is reduced for 5 h. The Pt content in the catalyst is 2 wt%.
[0027] The TEM image of the Pt / AC1 catalyst obtained in Example 1 at 20 nm is as follows: Figure 1 .
[0028] Example 2
[0029] A method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in water phase, comprising the following steps:
[0030] (1) Weigh 1 g of coconut shell activated carbon (specific surface area 1200 m 2 / g, pore volume is 0.4cm 3 / g, average pore size 2.5nm) was added to 30mL 4wt% HNO 3 Modification was performed in the solution, refluxed at 80°C for 0.5h under electromagnetic stirring, and after cooling to room temperature, washed with deionized water to neutrality, and dried to obtain pre-treated activated carbon;
[0031] (2) Weigh 1 g of potassium chloroplatinate hexahydrate and dissolve it in 16.5 mL of deionized water to obtain a precious metal impregnation solution;
[0032] (3) 2 mL of the noble metal impregnation solution was mixed with 1 g of pre-treated activated carbon, and the mixture was aged at room temperature for 15 h in a cool and dry place. The mixture was then crushed and placed in a muffle furnace. The temperature was raised to 400 °C at a rate of 1 °C / min and then air-baked for 5 h. After cooling to room temperature, H was introduced. 2 The volume content of H is 20%. 2 / N 2 The mixed atmosphere (the flow rate of the mixed atmosphere is 50 mL / min.) was heated to 300°C at a heating rate of 1°C / min for 5 hours to obtain a catalyst Pt / AC2. The Pt content in the catalyst is 4 wt%.
[0033] Example 3
[0034] A method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in water phase, comprising the following steps:
[0035] (1) Weigh 2 g coconut shell activated carbon (specific surface area 1500 m 2 / g, pore volume is 0.6cm 3 / g, average pore size of 2nm) was added to 80mL 5wt% HNO 3 The modified activated carbon was refluxed at 75°C for 1 h under electromagnetic stirring, cooled to room temperature, washed with deionized water until neutral, and dried to obtain the pre-treated activated carbon.
[0036] (2) Weigh 1 g of chloroplatinic acid and dissolve it in 38 mL of deionized water to obtain a precious metal impregnation solution;
[0037] (3) 2 mL of the noble metal impregnation solution was mixed with 2 g of pre-treated activated carbon, and the mixture was aged at room temperature for 16 h in a cool and dry place. Then, the mixture was crushed and placed in a muffle furnace. The temperature was raised to 500 °C at a rate of 2 °C / min, and then air-baked for 10 h. After cooling to room temperature, H was introduced. 2 The volume content of H is 20%. 2 / N 2 The mixed atmosphere (the flow rate of the mixed atmosphere is 40 mL / min.) was heated to 300° C. at a heating rate of 5° C. / min for 8 h to obtain a catalyst Pt / AC3. The Pt content in the catalyst is 1 wt%.
[0038] Example 4
[0039] A method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in water phase, comprising the following steps:
[0040] (1) Weigh 1 g of coconut shell activated carbon (specific surface area 1600 m 2 / g, pore volume is 0.7cm 3 / g, average pore size 2.5nm) was added to 25mL 4.5wt% HNO 3 The modified activated carbon was refluxed at 80°C for 2 h under electromagnetic stirring, cooled to room temperature, washed with deionized water until neutral, and dried to obtain the pre-treated activated carbon;
[0041] (2) Weigh 1 g of chloroplatinic acid and dissolve it in 19 mL of deionized water to obtain a precious metal impregnation solution;
[0042] (3) 0.5 mL of the noble metal impregnation solution was mixed with 1 g of pre-treated activated carbon, and the mixture was aged at room temperature for 6 h in a cool and dry place. Then, the mixture was crushed and placed in a muffle furnace. The temperature was raised to 500 °C at a heating rate of 3 °C / min and then air-baked for 8 h. After cooling to room temperature, H was introduced. 2The volume content of H is 10% 2 / N 2 The mixed atmosphere (the flow rate of the mixed atmosphere is 20 mL / min.), the temperature is raised to 300° C. at a heating rate of 5° C. / min, and the catalyst Pt / AC4 is reduced for 5 h. The Pt content in the catalyst is 3 wt%.
[0043] Example 5
[0044] A method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in an aqueous phase, comprising the following steps:
[0045] (1) Weigh 1 g of coconut shell activated carbon (specific surface area 1350 m 2 / g, pore volume is 0.5cm 3 / g, average pore size 2.2nm) was added to 35mL 3.5wt% HNO 3 The modified activated carbon was refluxed at 70°C for 2 h under electromagnetic stirring, cooled to room temperature, washed with deionized water until neutral, and dried to obtain the pre-treated activated carbon;
[0046] (2) Weigh 1 g of potassium chloroplatinite hexahydrate and dissolve it in 9.5 mL of deionized water to obtain a precious metal impregnation solution;
[0047] (3) 1 mL of the noble metal impregnation solution was mixed with 1 g of pre-treated activated carbon, and the mixture was aged at room temperature for 9 h in a cool and dry place. The mixture was then crushed and placed in a muffle furnace. The temperature was raised to 400 °C at a heating rate of 4 °C / min and then air-baked for 6 h. After cooling to room temperature, H was introduced. 2 The volume content of H is 20%. 2 / N 2 The mixed atmosphere (the flow rate of the mixed atmosphere is 35 mL / min.) was heated to 400°C at a heating rate of 4°C / min for 6 hours to obtain a catalyst Pt / AC5. The Pt content in the catalyst is 4 wt%.
[0048] The following experiments were carried out using the catalysts prepared in Examples 1 to 5:
[0049] 0.5 g of Pt / AC1 to Pt / AC5 catalysts were weighed respectively, and 15 mL of 2 wt% glucose aqueous solution was added to a 25 mL high-pressure reactor. The reactor was evacuated three times with high-purity oxygen, and finally filled with oxygen to 1 MPa and the reactor was sealed. The initial stirring speed was 200 rpm. After heating to 70 °C, the speed was increased to 1000 rpm and the timing was started. After 10 h of reaction, the solution components were analyzed by high performance liquid chromatography, and the conversion rate and selectivity were calculated. The specific results are shown in Table 1.
[0050] Table 1
[0051]
[0052] 0.5 g of Pt / AC1 to Pt / AC5 catalysts were weighed respectively, and 15 mL of 5 wt% ethylene glycol solution was added to a 25 mL high-pressure reactor. The reactor was evacuated three times with high-purity oxygen, and finally filled with oxygen to 1 MPa and sealed. The initial stirring speed was 200 rpm. After heating to 70 °C, the speed was increased to 1000 rpm and the timing was started. After 12 h of reaction, the solution components were analyzed by high performance liquid chromatography, and the conversion rate and selectivity were calculated. The specific results are shown in Table 2.
[0053] Table 2
[0054] catalyst Ethylene glycol conversion rate / % Glycolic acid selectivity / % Carbon Balance Pt / AC1 68.4 85.9 0.89 Pt / AC2 72.5 79.9 0.99 Pt / AC3 89.5 87.4 0.97 Pt / AC4 86.2 78.1 0.96 Pt / AC5 91.6 70.2 1.00
[0055] 0.5 g of Pt / AC1 to Pt / AC5 catalysts were weighed respectively, and 15 mL of glycerol solutions of different concentrations were added to a 25 mL high-pressure reactor. The reactor was evacuated three times with high-purity oxygen, and finally filled with oxygen to 1 MPa and sealed. The initial stirring speed was 200 rpm. After heating to 70 °C, the speed was increased to 1000 rpm and the timing was started. After 12 h of reaction, the solution components were analyzed by high performance liquid chromatography, and the conversion rate and selectivity were calculated. The specific results are shown in Table 3.
[0056] Table 3
[0057]
[0058]
[0059] 0.05 g of Pt / AC1 to Pt / AC5 catalysts were weighed respectively, and 15 mL of 3.5 wt% 1,2-propylene glycol solution was added to a 25 mL high-pressure reactor. The reactor was evacuated three times with high-purity oxygen, and finally filled with oxygen to 1 MPa and sealed. The initial stirring speed was 200 rpm. After heating to 70 °C, the speed was increased to 1000 rpm and the timing was started. After 10 h of reaction, the solution components were analyzed by high performance liquid chromatography, and the conversion rate and selectivity were calculated. The specific results are shown in Table 4.
[0060] Table 4
[0061]
[0062] 0.05 g of Pt / AC1 to Pt / AC5 catalysts were weighed respectively, and 15 mL of 3 wt% 1,2-butanediol solution was added to a 25 mL high-pressure reactor. The reactor was evacuated three times with high-purity oxygen, and finally filled with oxygen to 1 MPa and sealed. The initial stirring speed was 200 rpm. After heating to 70 °C, the speed was increased to 1000 rpm and the timing was started. After 12 h of reaction, the solution components were analyzed by HPLC, and the conversion rate and selectivity were calculated. The specific results are shown in Table 5.
[0063] Table 5
[0064]
[0065]
[0066] It can be seen from Examples 1 to 5 that the catalyst synthesized by the method of the present invention has mild reaction conditions in the selective oxidation of polyols and sugars, a wide range of application scenarios, high polyol or sugar conversion rate, high fruit acid selectivity, and high catalyst acid resistance and stability.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in an aqueous phase, characterized in that: The following steps are involved: (1) Activated carbon pretreatment: adding activated carbon to an acidic solution, heating under reflux under stirring conditions, then cooling to room temperature, washing with deionized water until neutral, and drying to obtain pretreated activated carbon; the ratio of activated carbon to acidic solution is 1 g: 20-40 mL; (2) Synthesis of acid-resistant solid catalyst: The pretreated activated carbon is added to the precious metal impregnation solution and mixed evenly, then aged at room temperature for 10 to 20 hours, taken out and crushed, calcined at elevated temperature, cooled, and reduced at high temperature to obtain the acid-resistant solid catalyst.
2. The method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in water phase according to claim 1, characterized in that: The activated carbon in step (1) is wood activated carbon; the activated carbon has an active specific surface area of 1200 to 1600 m 2 / g, pore volume is 0.4~0.8cm 3 / g, and the average pore size is 2 to 2.5 nm.
3. The method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in water phase according to claim 1, characterized in that: The heating reflux temperature in step (1) is 70-80° C., and the reflux time is 0.5-2 h.
4. The method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in water phase according to claim 1, characterized in that: The acidic solution in step (1) is at least one of a nitric acid solution, a sulfuric acid solution and a hydrochloric acid solution; the mass concentration of the acid in the acidic solution is 2-5%.
5. The method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in water phase according to claim 1, characterized in that: The precious metal impregnation solution in step (2) is an aqueous solution of a platinum salt; the platinum salt is at least one of potassium chloroplatinate, tetraammine platinum nitrate, platinum nitrate, potassium chloroplatinite, ammonium chloroplatinite, chloroplatinic acid, and platinum acetylacetonate; the mass concentration of platinum in the precious metal impregnation solution is 1 to 10%; the amount of the precious metal impregnation solution is added according to the mass percentage of the precious metal element in the catalyst of 0.2 to 20wt%.
6. The method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in water phase according to claim 1, characterized in that: The heating rate of the calcination in step (2) is 1.0-3.0°C / min, the temperature is 200-500°C, and the calcination time is 4-10h.
7. The method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in water phase according to claim 1, characterized in that: The high-temperature reduction in step (2) is carried out in at least one mixed atmosphere of H2 / N2, H2 / He, and H2 / Ar, the volume fraction of H2 in the mixed atmosphere is 10 to 30%, and the flow rate of the mixed atmosphere is 20 to 50 mL / min.
8. The method for synthesizing an acid-resistant solid catalyst for polyol oxidation reaction in water phase according to claim 1, characterized in that: The heating rate of the high temperature reduction in step (2) is 1.0-5.0°C / min, the temperature is 200-500°C, and the reduction time is 4-10h.
9. An acid-resistant solid catalyst for polyol oxidation reaction in water phase, characterized in that: The catalyst is prepared by the method described in any one of claims 1 to 8; The mass percentage of the noble metal element in the catalyst is 0.2-20wt%.
10. The use of the acid-resistant solid catalyst for polyol oxidation reaction in water phase according to claim 8, characterized in that: The catalyst is used for the oxidation reaction of a polyol in an aqueous phase, wherein the polyol is at least one of glycerol, ethylene glycol, propylene glycol, butylene glycol, pentanediol, hexanediol, glucose, mannose, and xylose; The temperature of the oxidation reaction is 50-120° C., the reaction time is 0.5-48 hours, and the oxygen pressure is 0.1-2.0 MPa.
Citation Information
Patent Citations
Active carbon loaded catalyst and preparation method and application thereof
CN102513100A
Load type spherical active carbon catalyst and preparation method thereof
CN104084195A
Preparation method of high-activity long-acting platinum-carbon catalyst
CN104667909A
Nitrogen-doped carbon-coated noble metal liquid phase hydrogenation catalyst, and preparation method and application thereof
CN113952977A
Papermaking black liquor lignin conversion catalyst as well as preparation method and application thereof
CN115672332A
Cited By
Hydrothermal-resistant and acid-resistant catalyst for efficiently catalyzing oxidation of polyol as well as preparation method and application of catalyst
CN120662331A